Sup-norm estimates for Bergman-projections on regulated domains - Erkkilä, Paula; Taskinen, Jari (MATHEMATICA SCANDINAVICA, 2008)
We give sufficient and necessary conditions for the boundedness of generalized Bergman projections on the space $L^∞_v(Ω)$. The conditions depend on the geometry of the simply connected domain $Ω \subset \mathsf C$.